Effect of empagliflozin on cytoskeletal repair in the hippocampus of obese mice - Chen, Xiaoyi; Ma, Liang; Zhao, Jingyu; Pan, Xiaoyu; Chen, Shuchun (Frontiers in Neuroscience, 2022)
Objective: We aimed to investigate the effect of empagliflozin on hippocampal phosphorylated protein levels in obese mice. Methods: Sixteen obese mice successfully modeled on high-fat diet were randomly divided into high-fat feeding group (group H) and engramine group (group H+engramine, group E), 8 mice in each group, and 8 C57BL/6J male normal mice were selected as the control group (normal control, group C). Group E was treated with engramine 10 mg/kg/d for 12 weeks, while mice in groups H and C were treated with equal amounts of saline. the spatial learning memory ability of the mice was determined by the Morris water maze experiment. Further, their body weights and serological indices were measured. Finally, total proteins were extracted from hippocampal tissues for functional analysis by the phosphorylated proteomics method.Results: The results showed that escape latency was prolonged, retention time in the target quadrant was shortened, and the number of loop penetrations was reduced in the obese mice induced by a high-calorie diet compared with normal controls, whereas escape latency was shortened, retention time in the target quadrant was increased, and the number of loop penetrations was increased after empagliflozin treatment. Phosphoproteomics in the high-fat/control (H/C), empagliflozin/high-fat (E/H), and E/C groups showed 844, 1,552, and 1,512 differentially significant phosphorylation sites, respectively. The proteins corresponding to these differentially phosphorylated sites were mainly involved in neurodegenerative pathways and actin cytoskeleton regulation. Notably, myosin heavy chain 10 (MYH10), p21 protein-activated kinase 4 (PAK4), phosphatidylinositol 3-phosphate 5-kinase (PIKfyve), and other differentially phosphorylated proteins were involved in actin cytoskeleton regulation. Conclusion: We concluded that empagliflozin protects cognitive functions by inducing serine phosphorylation in MYH10, PAK4, and PIKfyve in the hippocampal tissue of obese mice.